Foreign Worker Employment in Indonesia: Balancing Investment, Knowledge Transfer, and Local Labor Protection - Mashari, Mashari; Indriyasari, Indriyasari; Sriwati, Endah; MD Said, Muhamad Helmi (Jurnal Hukum, 2025)
This study examines Indonesia’s legal system for employing foreign workers, with a focus on how well it balances economic growth, protection of local workers, and national security. Using a normative juridical approach, it reviews main regulations such as the Immigration Law, the Manpower Law, and Government Regulation Number 34 of 2021. The research finds that the Foreign Worker Utilization Plan is an important tool, but its implementation is weak because of a lack of labor inspectors, poor coordination between institutions, and light sanctions. Although reforms like the Job Creation Law were introduced to make the process easier and attract investment, there are still conflicts between new and old rules, as well as limited public involvement. The study also shows that while foreign workers can support knowledge transfer, their long-term stay and work in low-skilled jobs often reduce opportunities for local workers. To solve these problems, the research suggests creating a stronger supervisory system that includes preventive, persuasive, and repressive measures, better coordination between institutions, and stricter penalties. These steps would help ensure that employing foreign workers benefits the economy while also protecting local workers and national interests.